Nose-to-brain Delivery of Natural Compounds for the Treatment of Central Nervous System Disorders - Bicker, Joana; Fortuna, Ana; Alves, Gilberto; Falcão, Amílcar (Current Pharmaceutical Design, 2020)
Background: Several natural compounds have demonstrated potential for the treatment of central nervous system disorders such as ischemic cerebrovascular disease, glioblastoma, neuropathic pain, neurodegenerative diseases, multiple sclerosis and migraine. This is due to their well-known antioxidant, anti-inflammatory, neuroprotective, anti-tumor, anti-ischemic and analgesic properties. Nevertheless, many of these molecules have poor aqueous solubility, low bioavailability and extensive gastrointestinal and/or hepatic first-pass metabolism, leading to a quick elimination as well as low serum and tissue concentrations. Thus, the intranasal route emerged as a viable alternative to oral or parenteral administration, by enabling a direct transport into the brain through the olfactory and trigeminal nerves. With this approach, the blood-brain barrier is circumvented and peripheral exposure is reduced, thereby minimizing possible adverse effects. Objective: Herein, brain-targeting strategies for nose-to-brain delivery of natural compounds, including flavonoids, cannabinoids, essential oils and terpenes, will be reviewed and discussed. Brain and plasma pharmacokinetics of these molecules will be analyzed and related to their physicochemical characteristics and formulation properties. Conclusion: Natural compounds constitute relevant alternatives for the treatment of brain diseases but often require loading into nanocarrier systems to reach the central nervous system in sufficient concentrations. Future challenges lie in a deeper characterization of their therapeutic mechanisms and in the development of effective, safe and brain-targeted delivery systems for their intranasal administration.
Keywords: Brain distribution